2014
DOI: 10.1128/cvi.00605-13
|View full text |Cite
|
Sign up to set email alerts
|

An Attenuated Duck Plague Virus (DPV) Vaccine Induces both Systemic and Mucosal Immune Responses To Protect Ducks against Virulent DPV Infection

Abstract: c Duck plague (DP) is a severe disease caused by DP virus (DPV). Control of the disease is recognized as one of the biggest challenges in avian medicine. Vaccination is an efficient way to control DPV, and an attenuated vaccine is the main routine vaccine. The attenuated DPV vaccine strain CHa is a modified live vaccine, but the systemic and mucosal immune responses induced by this vaccine have been poorly understood. In this study, the immunogenicity and efficacy of the vaccine were evaluated after subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 38 publications
6
29
0
Order By: Relevance
“…Post-immunization humoral level of immunity was assessed by measuring the titers of IgG and IgM using ELISA with the number of CD4 (+) T cells was found increased in contrast to the CD8(+) T cells through flow cytometry after immunization. These results support the subcutaneous route of administration for delivering attenuated vaccines (Huang et al 2014). Hence adopting an appropriate route of vaccination is an essential factor to elicit desired protective immunity.…”
Section: Vaccinationsupporting
confidence: 59%
See 1 more Smart Citation
“…Post-immunization humoral level of immunity was assessed by measuring the titers of IgG and IgM using ELISA with the number of CD4 (+) T cells was found increased in contrast to the CD8(+) T cells through flow cytometry after immunization. These results support the subcutaneous route of administration for delivering attenuated vaccines (Huang et al 2014). Hence adopting an appropriate route of vaccination is an essential factor to elicit desired protective immunity.…”
Section: Vaccinationsupporting
confidence: 59%
“…Live attenuated vaccines are considered most effective against DPV hence it is of foremost importance to maintain the vaccine at optimum physical and physiological conditions of temperature, salt and pH to prevent any loss in the activity of vaccine candidate molecule (Makhija & Kumar 2016). The vaccinated ducks could excrete the virus thus demands revaccination of the entire flock (Huang et al 2014).…”
Section: Vaccinationmentioning
confidence: 99%
“…Through clinical and pathological pictures that were examined under the experimental infection, infected-emergency vaccinated groups had clinico-pathological pictures lower than in infected-non-vaccinated group especially that vaccinated via subcutaneous route. This explained by Huang et al [14] who demonstrated that subcutaneous administration of the attenuated DEV vaccine could produce efficient humoral, cellular, and mucosal immune responses against DEV challenge. Also, Xiaoyan et al [35] proved that oral immunization with live attenuated DEV vaccine is effective in inducing mucosal immunity that is important in protecting animals from intestinal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization of ducks is an efficient tool to prevent DEV infection [13,14]. Live attenuated and/or an inactivated vaccines induced effective immune response in birds [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation